1994
DOI: 10.1163/22941932-90000611
|View full text |Cite
|
Sign up to set email alerts
|

Sem Observations on Perforated Ray Cells

Abstract: The occurrence and morphology of perforated ray cells in eight Yunnan hardwoods were investigated using SEM, and the micromorphology of their perforation plates compared with those in the vessel member end walls. In most cases the perforation plates were dimorphic with the total area of the openings in the perforated ray cells sm aller than the perforation plates in the vessel member ends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…McLean and Richardson (1973) suggested that perforated ray cells may function as a part of the vertical conducting system of the xylem and named them vascular ray cells. Although perforated ray cells are commonly confined to exclusively uniseriate rays or uniseriate extensions of tall multiseriate rays (Carlquist 1988;Nagai et al 1994;Eom & Chung 1996), they occasionally occur in the multiseriate portion of wide rays (Bottoso & Gomes 1982;Dayal et al 1984;Rao et al 1984). The diagnostic value of these cells has been questioned by several authors (Rudall 1985;Carlquist 1988;IAWA Committee 1989).…”
Section: Introductionmentioning
confidence: 99%
“…McLean and Richardson (1973) suggested that perforated ray cells may function as a part of the vertical conducting system of the xylem and named them vascular ray cells. Although perforated ray cells are commonly confined to exclusively uniseriate rays or uniseriate extensions of tall multiseriate rays (Carlquist 1988;Nagai et al 1994;Eom & Chung 1996), they occasionally occur in the multiseriate portion of wide rays (Bottoso & Gomes 1982;Dayal et al 1984;Rao et al 1984). The diagnostic value of these cells has been questioned by several authors (Rudall 1985;Carlquist 1988;IAWA Committee 1989).…”
Section: Introductionmentioning
confidence: 99%
“…According to observations by various authors, perforated ray cells may be located in a variety of areas: predominantly in the uniseriate margins of multi seriate rays (Chalk & Chattaway 1933;Norverto 1993); largely confined to uniseriate rays and to the uniseriate margins of multi seriate rays (Nagai et al 1994); located only in the multi seriate part of the rays (Botosso & Gomes 1982;Dayal et al 1984), or present as much in the body as in the uniseriate extensions (Eom & Chung 1996). Perforated ray cells of Saracha quitensis were noted more frequently in the uniseriate margins of multiseriate rays (Fig.…”
mentioning
confidence: 99%
“…In the species that have been studied, interpretations of PRC conductivity diverge. Nagai et al (1994) observed PRC resistance to sap flow much greater than that observed by Ceccantini & Angyalossy-Alfonso (2000), who suggest that Bathysa meridionalis has much lower resistance.…”
Section: Introductionmentioning
confidence: 73%
“…PCRs are relatively uncommon, and therefore often difficult to observe or quantify. For example, Flacourtiaceae and Saurauiaceae contain from 0-15 PRC cm -2 (Nagai et al 1994). Only 0-2 PRC cm -2 are usually observed in preparations which require substantial time and effort to prepare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation